(untitled) (Bangladesh Journal of Medical Science, 2013)
Foreign body in early pediatric life is common, owing to the childs developing dentition and maturity of swallowing mechanism. As the child grew older, the nature of foreign body inhaled might changed. Most of them are due to carelessness and improper habit of holding foreign material in between the lips. We report a case of a boy who inhaled a soft-board metal pin, which was retrieved after multiple attempts due to the nature of the pin that easily slipped and dislodged into distal bronchioles. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 238-239 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14981